Development Of A Nutritionallybalanced, Cost-Effective, Socially Acceptable And Sustainable Emergency Food Aid Design For Disaster Relief And Preparedness - Balachanthar, Satesh (2019)
Introduction: Addressing immediate food requirement, alleviating hunger and ensuring survival of the disaster victims remains the primary aim of emergency food aid. The lack of standardised emergency food aid policy in the country has led to the provision of inconsistent emergency food aid in terms of food type, energy and micronutrient content, and overall cost of food aid. The lack of transparent standard operating procedures involving food procurement, distribution and preparation also places the country at risk during disaster. Provision of emergency food aid targeting populations with diabetes mellitus, cardiovascular disease and chronic kidney disease is lacking and requires immediate attention. The objective of the study was to design a nutritionally-appropriate, cost-effective, socially-acceptable and sustainable emergency food aid. Methodology: Mixed methodology approach was employed in developing the emergency food aid plan targeting the following population: healthy, diabetes mellitus (DM), cardiovascular disease (CVD) and chronic kidney disease (CKD). Phase I primarily focused on developing 3-day emergency food menu using principles of dietetics and Nutritionist Pro software which addressing three scenarios: immediate food requirement (IFR); emergency food basket (EFB); and congregate feeding (CF) at the evacuation shelters.